'Primacy of the Ear' – But Whose Ear?: The case for auraldiversity in sonic arts practice and discourse. Issue 1 (30th May 2019) - Drever, John Levack
Abstract : Sixty years on from Pierre Schaeffer's call for 'primacy of the ear' ( primauté de l'oreille ), this article asks an ostensibly simple question: whose ear/aural perception is being referred to when we talk of and compose under this guiding principle? Is there a tacit preselected audiometric norm or even a pair of golden ears, at its core? The article will problematise the uncompromising modernist notion espoused by Babbitt of a 'suitably equipped receptor' (Babbitt 1958), and posit examples of well-known composers whose hearing markedly diverged from the otologically normal, an acoustics standard from which A-weighted decibels is predicated (ISO 226:2003). In conclusion the concept of auraldiverse hearing is proposed and creative strategies that eschew or problematise auraltypical archetypes in sonic arts practice and theory wherever they may lie are encouraged.